The Impact of New Financial Technologies on the International Financial Market as Exemplified by Postal Savings Bank of China Co., Ltd. - Zhengbo Yu; Anna Korenevskaya (Communications of International Proceedings, 2021)
In the modern world, new technologies (digital, telecommunications, biometric, etc.) are restructuring the financial services industry, actively replacing traditional players and traditional business models. The integration of new financial solutions allows you to change the structure of consumption, reduce the cost of certain functionality (processing customer bases, loyalty programs), increase the efficiency and quality of business processes (targeting the target audience, scoring), and also significantly influence the sustainability of the core business, etc. [2] The global financial technology market is one of the fastest growing in the world. The number of users of financial technologies in the world, according to expert estimates, annually grows by 15–20%, which is actively promoted by the growth of Internet penetration in the world [3]. The key prerequisites for the emergence of a tech industry in China are a high level of Internet penetration and its availability to wide categories of the population, low margins of banking products and services. A feature of financial technologies in China is the concentration of technological competencies directly in the banking system. Banks themselves are actively introducing financial technologies, buying promising startups or entering into strategic partnerships. In China, a segment of neobanks (banks with a traditional set of services) is gradually developing - a new force in the financial and technological industry, which in the future should change the balance of power in the global financial sector. Online lending is one of the key products in today's financial and technology market. The areas that tech banks and Chinese fintech companies are working on are payments and transfers, digital banking, finance, wealth management, business support, insurance, and regulatory technologies. The most promising segments that will actively develop in the near future in China are payments and transfers, financing, wealth management and insurance.
Keywords: Financial Technologies; Banking System; Financial and Technological Industry; Payment System; Financial Market.